(untitled) (Annals of Medical Research, 2021)
Aim: Primary hyperparathyroidism is a clinical condition caused by excessive parathyroid secretion of the parathyroid glands and related hypercalsemia. Hyperparathyroidism is a common cause of hypercalcemia. In this study, we aimed to present the results of patients operated on due to parathyroidadenoma in our clinic.Material and Methods: IPatients who underwent surgery for parathyroid adenoma in our clinic between January 2007 and January 2019 were included in the study. Clinical characteristics, biochemical data, treatment methods and results of the patients were analyzed retrospectively.Results: 156 patients with a mean age of 50.8 years participated in the study. Female sex was 76.2%. Preoperative calcium level was found as 11.2+1.02 mg/dl, Parathormone level was found as 114.7+109.5 pg / ml. The most common clinical presentation was asymptomatic hypercalcemia (48.7%). While 89.7% of the patients had only parathoridectomy, 3.2% had total thyroidectomy and 7.1% had lobectomy due to associated thyroid pathology (10.3%). Intraoperative rapid parathormone was used in 54.4% of the patients. Frozen examination was performed in all patients. The most common localization was inferior left 39.7%. The most common ectopic localization was intratymic at 2.6%. The mean duration of postoperative hospital stay was 3.81+2.69 days. Three patients (1.9%) had persistent hyperparathyroidism and 6 patients (3.8%) had recurrent hyperparathyroidism. The mean follow-up was 57.2+39.5 months. Conclusion: Proper preoperative evaluation, careful exploration, frozen examination and rapid parathormone test increase the success of parathyroid adenoma surgery.